THE CORRELATION BETWEEN PRESENT TENSE MASTERY AND THE WRITING ABILITY OF DESCRIPTIVE TEXT OF NINTH GRADE STUDENTS AT SMPN 19 PALEMBANG - R.M. Syafruddin; Aigen Pausel (Jurnal Didascein Bahasa, 2019)
The aim of this study was to find out whether there was significant correlation or not between present tense mastery and writing ability descriptive text. The population was the ninth grade students with the total 253 students from 9 classes at SMPN 19 Palembang. To select the sample of this study, purposive sampling technique was implemented. There were 111 students as sample. The data were selected from students’ present tense score and their writing descriptive text score. In analyzing the data, correlation analysis was used. Based on the statistical analysis, it was found that the correlation coefficient or the r-value (0.609) was higher than r-table (0.186). Then, the level of probability (p) significance (sig.2-tailed) was 0.000. It means that p-value (0.000) was lower than 0.05. It can be concluded that there was high significant correlation between the students’ present tense mastery and writing ability of descriptive text.